Research on the Analysis and Evaluation of Risk Factors for Gas and Coal Spontaneous Combustion in Large-Scale Goaf Areas - He, Shudong (International Journal of Natural Resources and Environmental Studies, 2024)
In response to the potential hazards of spontaneous combustion and gas in large-scale goaf areas, the risk factors such as coal spontaneous combustion status, gas status, and ventilation status in goaf are analyzed. And simulation software is used to simulate the internal flow field of large-scale goaf, and the distribution law of its internal flow field is obtained. Then, the index evaluation method is used to conduct special evaluations of spontaneous combustion risk and gas risk in large-scale goaf areas. Finally, based on the determination of the warning indicators, levels, rules, and warning signals for large-scale goaf hazards, the results of the special evaluation of goaf hazards are transformed into corresponding warning signals for release, forming a set of large-scale goaf hazard analysis and evaluation technology system.